SEARCH FOR PRACTICAL AND THEORETICAL SOLUTIONS TO THE PROBLEMS OF MULTICULTURALISM IN KAZAKHSTAN - Sarkulova M.S.,; Amen A. Zh. ,; Sarkulova Galiya , (Scientific Journal of Pedagogy and Economics, 2021)
The national development of any multicultural society is associated with a number of problems and challenges, because such a society is a set of different cultures that exist in one space and means the ability of people of different national, religious and cultural backgrounds to live in a single territory. In this regard, the problem of interaction of cultures is relevant, as well as questions about the role and place of individual cultures in a multicultural society, the degree and mechanism of their interaction. The issue of multicultural interaction is an important aspect of domestic research. Kazakhstan requires a reflexive understanding of not only the traditions of Kazakh culture, but also the phenomenon of multiculturalism in Kazakhstani society. In the post-Soviet period, our country has experienced severe emotional and psychological stress that has affected all aspects of society. These changes have led to a change in the attitude of the Kazakh people to other nationalities. The issues of tolerance and multiculturalism are especially relevant in the context of growing interethnic tension, ethnophobia and intolerance in the socio-economic and spiritual life of modern Kazakhstan. Thus, the problem of multiculturalism is associated with the search for practical and theoretical solutions to the problems facing the world community today. The active process of globalization raises the issue of conformity. The policy of identity is a response to the special effects of globalization: conflicts can arise between people who claim to live in a global world and those who live in a local culture. The relationship between global and local initiatives cannot be characterized by mergers or prohibitions. However, the diversity of society and culture will not disappear with globalization. Accordingly, the conflict between people who think in the global world and those who identify themselves with the local subculture is a conflict of multiculturalism and identity. As we all know, the core of identity is traditional and national culture, which is the most difficult test of globalization. Dialogue and cultural continuity are the main means of preserving identity. Elements of multiculturalism can be noted in Kazakhstan today. It can be attributed, first of all, to a multinational community, in which some subjects are divided according to the strength of their national traditions, cultural identity.